2004
DOI: 10.1111/j.1365-2125.2004.02131.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide in active rheumatoid arthritis: a prospective study in daily practice

Abstract: Aims  We prospectively studied the efficacy, incidence of adverse drug reactions and withdrawal from leflunomide in an outpatient population with rheumatoid arthritis in a setting of care‐as‐usual.Methods  In this prospective case series study, a standard dataset was collected from outpatient medical records, including patient and disease characteristics, data on leflunomide use and adverse drug reactions.Results  During the study period 136 rheumatoid arthritis patients started leflunomide. Median (range) fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
2
10
1
5
Order By: Relevance
“…Van Roon et al. 2 also showed a similar figure of ∼42%, which is much lower than 71% in our study at 2 years. There were no studies to compare 5‐year survival of leflunomide.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Van Roon et al. 2 also showed a similar figure of ∼42%, which is much lower than 71% in our study at 2 years. There were no studies to compare 5‐year survival of leflunomide.…”
Section: Discussionsupporting
confidence: 53%
“…All studies showed a high rate of gastrointestinal adverse effects, consisting of diarrhoea, nausea and elevated transaminases 2,7,8 . Interestingly, our study did not show any cardiovascular side‐effects.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations